PEREMPUAN DAN LITERASI MEDIA - Liliek Budiastuti Wiratmo (Yinyang: Jurnal Studi Islam Gender dan Anak, 2015)
The growth of media industry, both press and broadcasts (radio and television) increase the competition of media content toreach a large number of audiences through variety of rubric and broadcast programs. But this competetition doesn’t followed with a goodand save to consume content quality. Now on, female become the marketing frontline as well as product target that the media offer. To facethat condition, female need to have a good acknowledge about media industry so they can filter the offered informations